Review of the synthesis of acyclic and cyclic oxime ethers - Mirjafary, Zohreh; Abdoli, Morteza; Saeidian, Hamid; Kakanejadifard, Ali; Farnia, S. Morteza F (RSC advances, 2016)
Oxime ethers have attracted much attention due to their potential biological activities and wide variety of synthetic applications. Developing more efficient methods for the synthesis of oxime ethers has been the subject of numerous of papers in recent years. This review surveys literature methods for the synthesis of acyclic and cyclic oxime ethers. Oxime ethers have attracted much attention due to their potential biological activities and wide variety of synthetic applications.